Solid-state recycling of light metals: A review - Shamsudin, Shazarel (2016)
This article provides an intensive review of the past and current research work on the solid-state recycling of light metals. The review includes an experimental aspect of the relevant works that clearly clarify the effects of several critical factors noted as chip preparation, reinforcing phases, die geometry, process parameter selection and performance of miscellaneous methods over the quality of the extruded profiles. Likewise, reviews of numerical and analytical works on the solid-state recycling were presented to understand the strengthening phenomena of chip-based billet through the plastic deformation. Finally, concluding remarks underline challenges of direct recycling method and subsequently highlight the potential future work on making the method as a promising alternative for sustainable manufacturing agenda.